2022
DOI: 10.1002/aet2.10812
|View full text |Cite
|
Sign up to set email alerts
|

Systematic online academic resources (SOAR) review: Sickle cell disorders

Abstract: Background Free open‐access medical education (FOAM) resources have become highly utilized resources in emergency medicine education. However, FOAM content often lacks the traditional peer review process, leaving quality assessment to the readers. In this systematic online academic resource (SOAR) review, we apply a systematic methodology to assess the quality of FOAM resources on sickle cell disease (SCD). Methods We searched keywords for SCD using FOAM Search and the top 50 FOAM websites listed on the Social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…This is particularly important given the burgeoning number of pediatric nurse practitioner FOAM content creators and aggregators. 44,45 As noted in the prior SOAR reviews, [19][20][21] resources as a whole were found to have scored the lowest in the two questions related to the "review" domain of the rMETRIQ tool, Q6 (editorial process and peer review) and Q7 (postpublication commentary). Much has been written on the differences of FOAM resources in their editorial and peer review process.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…This is particularly important given the burgeoning number of pediatric nurse practitioner FOAM content creators and aggregators. 44,45 As noted in the prior SOAR reviews, [19][20][21] resources as a whole were found to have scored the lowest in the two questions related to the "review" domain of the rMETRIQ tool, Q6 (editorial process and peer review) and Q7 (postpublication commentary). Much has been written on the differences of FOAM resources in their editorial and peer review process.…”
Section: Discussionmentioning
confidence: 84%
“…19 The previous reviews covered the topics of renal and genitourinary 19 ; endocrine, metabolic, and nutritional disorders 20 ; and sickle cell disorders in adults. 21 These reviews utilized the revised METRIQ (rMETRIQ) score, a rating tool created from a rigorous derivation process, to assess the quality of blog posts. 15,22 In these reviews, authors found that a minority of resources assessed were of high quality (10%-16%).…”
Section: Foam Materials and The Ongoing Work Of The Medical Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Thus far, reviews have been performed for renal, endocrine, and sickle cell diseases for the SOAR bank of reviews. [13][14][15] This review focuses on acute gastrointestinal (GI) conditions relevant to EM.…”
Section: Introductionmentioning
confidence: 99%